2022
DOI: 10.1093/jnci/djac127
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Telephone-Based Smoking Cessation Treatment in the Lung Cancer Screening Setting

Abstract: Background Lung cancer mortality is reduced via low-dose CT screening and treatment of early-stage disease. Evidence-based smoking cessation treatment in the lung screening setting can further reduce mortality. We report the results of a cessation trial from the NCI’s SCALE collaboration. Methods Eligible patients (N = 818) aged 50–80 were randomized (May 2017-January 2021) to the Intensive vs. Minimal arms (8 vs. 3 phone ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 65 publications
3
41
0
Order By: Relevance
“…We used data collected from a randomized clinical trial in the lung cancer screening setting. One-half of the trial participants were not ready to quit within the next 30 days ( 37 ), similar to the US population of smokers eligible for lung cancer screening ( 5 , 12 ). Therefore, this study provides unbiased and generalizable results on the efficacy and costs of a smoking cessation intervention in the lung cancer screening setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used data collected from a randomized clinical trial in the lung cancer screening setting. One-half of the trial participants were not ready to quit within the next 30 days ( 37 ), similar to the US population of smokers eligible for lung cancer screening ( 5 , 12 ). Therefore, this study provides unbiased and generalizable results on the efficacy and costs of a smoking cessation intervention in the lung cancer screening setting.…”
Section: Discussionmentioning
confidence: 99%
“…The trial data were used to estimate cessation rates among lung screening participants ( 37 ). Because the trial did not have a no-intervention arm, we used self-reported data from the Tobacco Use Supplement to the Current Population Survey 2018-2019 to estimate rates expected without specific intervention ( Supplementary Methods ; Supplementary Table 1 , available online) ( 44 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al, (37) randomised 92 smokers attending screening to receive 6 sessions of telephone behavioural counselling after participants had attended screening and received results, or a written information booklet (UC). A subsequent paper from that group randomised 818 smokers to receive intensive (8 telephone counselling sessions plus 8 weeks of NRT patch) or less intensive (3 counselling sessions, plus 2 weeks NRT patch), delivered 13 days post LDCT scan (38). Williams et al, (41) randomised 315 smokers attending a TLHC to receive 6 sessions of telephone behavioural support starting immediately, with pharmacotherapy prescriptions within 48 hours of participating in the TLHC, or VBA to quit and signposting to local services (UC).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…To analyse the effectiveness of smoking cessation interventions, we performed a metaanalysis on included RCT which compared quit rate between smoking cessation and usual care groups delivered in a screening context. Meta-analysis of 8 RCTs eligible for inclusion (32,33,(35)(36)(37)(38)(39)41) (n= 1,984) demonstrated that providing a smoking cessation intervention improved quit rates among current smokers enrolled in screening programmes compared with usual care (OR: 2.01, 95%: 1.49-2.72 p<0.001), Figure 2. We included data from Arm 1 (e-cigarette with nicotine) and Arm 3 (usual care) from the Lucchiari et al, (35) study, as this best answered the research question.…”
Section: Effect Of Stop Smoking Interventions On Quit Rate Compared T...mentioning
confidence: 99%